Electromechanical processes during the start of induction-type magnetic levitation - Bolyukh, V. F. (Національний технічний університет "Харківський політехнічний інститут", 2025)
A study of induction-type magnetic levitation by determining the electromechanical processes that occur when a stationary inductor is connected to an alternating voltage source and the levitation of an anchor made in the form of a multi-turn shortcircuited winding with an attached load. Methodology. Using a mathematical model describing an inductor and an anchor with concentrated parameters, solutions are presented for equations describing the interconnected electrical, magnetic, mechanical and thermal processes that occur in induction-type magnetic levitation. Results. The influence of the frequency of the alternating current source on the electromechanical processes oflevitation, which occur at different parameters of the anchor, is established. Due to the phase delay of the induced anchor current in relation to the inductor current, an electrodynamic force directed downwards arises at certain moments of their period. The total force acting on the anchor, due to the electrodynamic component, is of an alternating nature with a predominance of the positive, upwardly directed component, which causes pulsations of the anchor speed. Originality. The force acting on the anchor due to the electrodynamic component is of an alternating nature with the positive component directed upwards dominating. The resulting oscillatory damping mechanical process occurs with an increase in the oscillation period and a decrease in its amplitude. Practical value. It has been established that the maximum value of the lifting force acting on the anchor is achieved at an alternating current frequency in the range from 75 to 125 Hz, and the highest value of the steady-state levitation height is realized for an anchor similar to an inductor at a frequency of 75 Hz.

Дослідження магнітної левітації індукційного типу шляхом визначення електромеханічних процесів, що виникають при підключенні нерухомого індуктора до джерела змінної напруги та левітації якоря виконаного у вигляді багатовиткової короткозамкненої обмотки з приєднаним навантаженням. Методологія. За допомогою математичної моделі, яка описує індуктор та якір із зосередженими параметрами, представлені рішення рівнянь, що описують взаємопов’язані електричні, магнітні, механічні та теплові процеси, що виникають у магнітній левітації індукційного типу. Результати. Встановлено вплив частоти джерела змінного струму на електромеханічні процеси левітації, що виникають за різних параметрів якоря. Через фазову затримку індукованого струму якоря по відношенню до струму індуктора в певні моменти їх періоду виникає електродинамічна сила спрямована вниз. Сумарна сила, що діє на якір, через електродинамічний складник, носить знакозмінний характер з переважанням позитивної, спрямованої вгору складової, що обумовлює пульсації швидкості якоря. Оригінальність. Діюча на якір сила через електродинамічну складову носить знакозмінний характер з переважанням позитивної, спрямованої вгору складової. Виникаючий при цьому коливально загасаючий механічний процес відбувається зі збільшенням періоду коливань та зменшенням його амплітуди. Практична цінність. Встановлено, що максимальна підйомна сила, що діє на якір, досягається при частоті змінного струму в діапазоні від 75 до 125 Гц, а найбільша висота левітації, що встановилася, реалізується для якоря, аналогічного індуктору, при частоті 75 Гц.
Keywords: magnetic levitation of induction type; mathematical model; experimental test; starting electromechanical characteristics; oscillatory electromechanical process; магнітна левітація індукційного типу; математична модель; експериментальне випробування; пускові електромеханічні характеристики; коливальний електромеханічний процес